ANALYSIS OF THE INFLUENCE OF REGULATION AND MANAGEMENT INFORMATION SYSTEM ON ASSET MANAGEMENT (EMPIRICAL STUDY ON UPT RADIO SPECTRUM MONITORING, DIRECTORATE-GENERAL OF POSTS AND INFORMATICS RESOURCES) - Imalia, Norma; Mattulada, Andi; Haris, Nurhayati (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aimed to determine the effect of Regulation and Information Systems on Asset Management. This research applied multiple regression analysis method where sampling technique used systematic sampling with purposive sampling. Based on the results of statistical tests, regulations and information systems have an influence on asset management at the UPT Radio Frequency Spectrum Monitoring, Directorate-General of Posts and Informatics Resources. The regulation partially has an influence on asset management at the UPT Radio Frequency Spectrum Monitoring, Directorate-General of Posts and Informatics Resources. The information system partially has an influence on asset management at the UPT Radio Frequency Spectrum Monitoring, Directorate-General of Posts and Informatics Resources. Keywords: Regulation, Information Systems, Asset Management.